Electronic Commerce: a battle on regulation, standards transportation media and business integration - Andersen, Kim; Bjorn-Andersen, Niels; Juul, Niels (Australasian Journal of Information Systems, 1998)
The drive towards the electronic commerce organisation is both a troublesome and a strifted path for government, enterprises and consumers worldwide. In this article we analyse the evolution of electronic commerce in Denmark during the period 1995-1998 from four perspectives: regulation, standards, transportation media and business integration.The Danish government is stimulating the use of electronic commerce using direct and indirect policy initiatives on central, governmental regulation and establishment of greens enabling self-regulation. Also, the governments own, organisational management is in Denmark seen as a mean to exalt electronic commerce.Onwards, the fist on proprietary standards and the UN/EDIFACT is an ongoing source of delaying, stimulating or reventing electronic commerce depending on the business sector and the size of market actor addressed. In Denmark, the direct access and value added network supporters have so far been the dominating mean to transport the electronic documents in the business transaction. The Internet and XML technology is at the turn of the century challenging the way of doing business within this field. Some view this as the big blue to speed the diffusion of electronic commerce; others are worried that the incentive to investment and pull the partners in the value chain to use EDI might be lost. Finally, our study conclude that the debate on business integration issues is ambiguous and characterised by substantial uncertainty on for example the role of intermediates, direct sale, hyper-shift in business partners and the pull/push of global enterprises at the local markets.